Pharyngolaryngeal manifestations of post-polio syndrome - De Biase, Noemi Grigoletto; de Moraes, Bruno Teixeira; Leb, Mariana Dantas Aumond; Korn, Gustavo Polacow; Padovani, Marina; Moraes, Miriam; Madazio, Glaucya (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The post-polio syndrome (PPS) is characterized by a new episod of atrophy or muscle weakness in individuals previously affected by poliomyelitis. The symptoms start from an extended period of clinical stability ranging from 20 to 40 years, after the initial chart of polio. Among the pathophysiological mechanisms, the most likely is that the syndrome represents a process of attrition and neuronal metabolic exhaustion due to a continuous process of denervation reinnervation which begins after the initial acute.Objective: Review the clinical characteristics and pathophysiological of PPS,as well as present the approach in cases with pharyngolaryngeal manifestations.Case Report: We present the clinical case of a male patient with 48 years old, with main complaints of dysphonia, dysphagia and previous history of polio. The patient underwent a diagnostic investigation, in which the voice psychoacoustic findings are described. Laringoscopic, electromyographic and the videoendoscopy of swallowing compatible with PPS. The treatment consisted in phonotherapy in a total of 11 weekly sessions and guidelines for swallowing, with satisfactory improvement of the symptoms.Final comments: The pharyngolaryngeal manifestations of PPS are susceptible to treatment, obtaining satisfactory results, with improvement of life quality of the patients.
Keywords: poliomyelitis; post-polio syndrome; neuromuscular diseases; larynx diseases; voice disorders.